Heterogeneity of antifreeze polypeptides from the Newfoundland winter flounder, Pseudopleuronectes americanus - Fourney, Ron M.; Joshi, Shashikant B.; Kao, Ming H.; Hew, Choy L. (Canadian Journal of Zoology, 1984)
The heterogeneity of Newfoundland winter flounder antifreeze polypeptides was analyzed by reverse phase high performance liquid chromatography and by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Seven antifreeze polypeptide components could be readily demonstrated. Five of the components were similar in molecular weight (3300) and amino acid composition. Two of the antifreeze polypeptide components were larger (4500) and contained valine. The two major components (components 6 and 8) were identical to those reported earlier from our laboratories.